?????? ??????? ??????? ????????? " ?????? ????? ????? ????" ?????? ????? ??????? ????? ????? ?????? ?????? ???? ??????? ???????? ????? ???????? - Ibnu Makruf; Mohammad Nu’man; Aan Najib (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2017)
The purpose of learining Arabic is to master all four language skills, listening, speaking, reading dan writing skills. Most students have difficulty to mastering writing skills. Difficulties in mastering writing skills were also felt by Sabilul Muttaqin High School students in Pungging Mojokerto. It can be seen from the Arabic test scores of students who still have not reached the KKM (Minimum Completation Criteria) 75. Based on these problems, researchers want to use tondo maker comic learning media to improve students’ writing skills in Arabic lessons. This study uses a quantitative method to determine the effectiveness of the comics tondo maker media to improve Arabic writing skills. This research was conducted at Sabilul Muttaqin Mojokerto High School with tenth grade as a sample 66 students. In an effort to collect data, researchers used the method of observation, interviews, documentation, questionnaires and test. The results of this study indicate that the tondo maker comic media is effective in an effort to improve student writing skills based on the results of T count is 3,255 greater than T table, which is 2,30. From these results indicate that Ho is rejected and the results of sig Tailed 0.003 is smaller than 0.005 which indicates Ho’s rejection and Ha’s acceptance.